Influence of the time of fungicide application in the production of trichothecenes on field inoculated spikes from wheat grown in Argentina - Pesquero, Natalia; Ramirez Albuquerque, Diana; Rojas, Dante Emanuel; Alberione, Enrique Javier; Rodriguez, Anabel; Moschini, Ricardo; Fernandez Pinto, Virginia (Springer, 2021)
Fusarium graminearum is considered the main causative agent of Fusarium Head Blight in wheat. The fungus produces mycotoxins of the trichothecene family that pose a significant threat to the health of animals and humans. The objective of this work was to analyze the effect of the time of fungicide application on the trichothecene production in 8 inoculated wheat varieties. The fungicide Tebuconazole was applied in two independent stages: immediately after inoculation and after 72 h of the inoculation (infective event derived from 72 h of wetting). The detection of mycotoxins was performed by gas chromatography with electron capture detector and the results were confirmed by gas chromatography coupled to a mass spectrometer. Significant levels of deoxynivalenol were found in all samples and in almost all of them 15 acetyldeoxynivalenol was found in low concentration. Less frequently, 3 acetyldeoxynivalenol was found in higher values. There were not significant differences (p > 0.05) between the time of fungicide application (immediately after inoculation in anthesis and after 72 h) in all wheat varieties studied. The expansion of the fungicide application window for effective control of trichothecenes for 72 h represents an economic advantage for the producer avoiding the use of agrochemicals by preventive applications and minimizing the risk on human health and the environment.